2015
DOI: 10.1186/s13104-015-1343-1
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis of individual and community level factors associated with institutional delivery in Ethiopia

Abstract: BackgroundImproving maternal health is one of the eight millennium development goals to reduce maternal mortality (MM) by three quarters between 1990 and 2015. Institutional delivery is considered to be the most critical intervention in reducing MM and ensuring safe motherhood. However, the level of maternal morbidity and mortality in Ethiopia are among the highest in the world and the proportion of births occurring at health facilities is very low. This study examined the individual and community level factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
67
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(108 citation statements)
references
References 37 publications
39
67
2
Order By: Relevance
“…The findings showed that woman's had more educated, more likely to deliver by c-section. This result lower than and consistent with previous findings [1,13,19,20].The possible reasons could be, educated woman's might search a means to minimize absorbate and more worry their health. The difference might be sample size.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The findings showed that woman's had more educated, more likely to deliver by c-section. This result lower than and consistent with previous findings [1,13,19,20].The possible reasons could be, educated woman's might search a means to minimize absorbate and more worry their health. The difference might be sample size.…”
Section: Discussionsupporting
confidence: 90%
“…Surprisingly, the finding revealed that number of ANC had not statistically significant effect on csection. The results consistent a study conducted in Wolayta Sodo [20,23]. The reasons could be they consult skilled person if they start ANC earlier.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The possible reason behind this could be, the characteristics that predispose women to seek ANC service could also make them more likely to seek PNC service. Besides, those women who were using ANC service could be familiar with other maternal health service and it might also create an opportunity for health professionals to provide counseling regarding the significance of PNC services [23,33]. The household wealth index was another positively associated variable.…”
Section: Discussionmentioning
confidence: 99%
“…The factors which determine the utilization of PNC services differ from place to place, from individual to community which is affected by the culture and belief of women [18][19][20][21][22][23][24]. Even though the factors for PNC service utilization were from different levels, those previous studies conducted in Ethiopia simple regression model of analysis and the sample sizes were covering only specific or local areas [25][26][27].…”
Section: Introductionmentioning
confidence: 99%